ANALISIS SISTEM ANTREAN PELAYANAN DI PT POS INDONESIA (PERSERO) KANTOR POS II SEMARANG - Anggraini Susanti Kusumawardani; Sugito Sugito; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
PT Pos Indonesia (Ltd.) is one of state-owned enterprise engaged the field of service. Along with the development of communication device which more sophisticated and modern, PT Pos Indonesia (Ltd.) has to restructure, reform, and transform. Hence, that mail and delivery service through post remains used and preferred by community. There are many things to do by the customers, this is the reason why PT Pos Indonesia (Ltd.) Kantor Pos II Semarang is always crowded by customers. Therefore, it’s important to analyze queuing system that describe the condition of service line and measures of performance of four types of service counters in PT Pos Persero (Ltd.) Kantor Pos II Semarang, those are Postage counter, Special Delivery, Express, and EMS counter, Money Orders counter, and Tax counter. Base on the observation that has been done, the queuing model at the Postage counter is (M/G/1):(GD/∞/∞), Special Delivery, Express, and EMS counter is (M/M/3):(GD/∞/∞), Money Orders counter is (M/M/2):(GD/∞/∞), and Tax counter is (M/M/2):(GD/∞/∞). Key words : PT Pos Indonesia (Ltd.) Kantor Pos II Semarang, Queuing Model, Measures of Performance.